Leading by words: A voluntary contribution experiment with one-way communication - Anastasios Koukoumelis; Maria Vittoria Levati; Johannes Weisser (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
In this paper, we study a voluntary contribution mechanism with one-way communication. The relevance of one person's words is assessed by assigning exogenously the role of the communicator to one group member. Contrary to the view that the mutual exchange of promises is necessary for the cooperation-enhancing effect of communication, we ï¬nd that, compared to a standard voluntary contribution mechanism with no communication, one-way communication signiï¬cantly increases contributions and renders them stable over time. Moreover, the positive effects of one-way communication persist even when communication is one-shot.
Keywords: C72; C92; H41; 330; Public goods experiment; computer-mediated communication; Cheap-talk; Cooperation; Öffentliches Gut; Nichtkooperatives Spiel; Test; Kommunikation; Computergestütztes Verfahren